Urea pipe
By using modified nylon 6 and ethylene propylene ternary rubber in urea tubes, combined with nano zinc oxide and epoxy modified polytetrafluoroethylene, the crystallization problem of urea tubes in low temperature environments is solved, and the heat resistance, corrosion resistance and mechanical properties are improved to meet the use needs in high-temperature and high-corrosion environments.
Patent Information
- Application Number
- CN202510136934.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-07
- Publication Date
- 2025-03-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The urea solution in existing urea tubes is prone to crystallization in low temperature environments, resulting in jet and flow barriers. It has poor heat resistance and average corrosion resistance, making it difficult to meet the needs of use in high temperature and high corrosion environments.
Nylon 6 is used as the matrix, combined with modified ethylene propylene ternary rubber and epoxy modified polytetrafluoroethylene, and dispersing nano zinc oxide and γ-methacryloyloxypropyl trimethoxysilane by ultrasonic to form modified zinc oxide, which enhances the mechanical and corrosion resistance of the material.
It significantly improves the heat resistance, corrosion resistance and mechanical properties of urea tubes, extends the service life, and maintains stable performance in high temperature and high corrosion environments.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of automobile urea pipes, in particular to a urea pipe. Background Art
[0002] SCR is an exhaust gas aftertreatment system, namely the automobile selective catalytic reduction system. The basic principle is to use ammonia as a reducing agent to convert harmful NO in diesel engine exhaust into x Converted into harmless nitrogen and water vapor. The SCR system consists of a urea tank assembly, an SCR catalyst assembly, a urea pump assembly, a DCU, a urea injector, an injector mounting assembly, a sensor, an electrically heated urea pipe, and a wiring harness. The urea pipe is a pipe used to transport urea solution in the SCR. In a low-temperature environment, the urea solution will crystallize, causing the urea to be unable to spray and flow normally, causing the vehicle's SCR system to stop working and the vehicle to be unable to operate normally. Therefore, the delivery pipeline must also have the function of low-temperature thawing, and a heated urea pipe is required to melt the crystallized urea into a liquid solution.
[0003] Urea pipes are in a high temperature environment, so they have high requirements for heat resistance and aging resistance. At the same time, urea pipes need to have excellent resistance to urea corrosion and lubricating oil. Existing urea pipes are basically made of nylon 6, which has the characteristics of good wear resistance and high strength. It is an important engineering plastic. However, when the temperature is too high, the pressure resistance of nylon pipes decreases, affecting its bending resistance. It is easy to get clogged after bending, affecting performance, and its aging resistance is average. Rubber material has the advantage of high elasticity. It is not easy to bend and easy to recover after bending. Chinese patent application CN102585380A discloses a urea pipe and its production process. The main material of the urea pipe is EPDM rubber, and zinc oxide, stearic acid, phenolic resin, white carbon black, antioxidant, silicon aluminum carbon black, calcium carbonate, polyethylene wax, vulcanizing agent S, accelerator DM, accelerator TMTD, accelerator DTDM, accelerator PZ, and anti-scorch agent are added. The obtained urea pipe has excellent heat resistance, automotive urea resistance, and lubricating oil resistance, but its mechanical strength is low and the raw material dispersion is general, which is difficult to meet people's needs.
[0004] Therefore, developing a urea tube with excellent comprehensive performance has become a hot topic in current research. Summary of the invention
[0005] 1. Technical issues to be resolved In order to solve the above technical problems, the present invention provides a urea pipe, which solves the problems of poor heat resistance and general corrosion resistance of the urea pipe, and provides a urea pipe with good heat resistance, excellent corrosion resistance and excellent mechanical properties.
[0006] (II) Technical solution In order to achieve the above object, the present invention discloses a urea tube, which comprises the following raw materials in parts by mass: 100 parts of nylon 6, 25-42 parts of EPDM rubber modified nylon 6, 7-12 parts of epoxy modified polytetrafluoroethylene, 0.2-0.5 parts of antioxidant, 0.5-1 parts of lubricant, and 0.1-0.5 parts of dispersant; The urea tube is prepared by the following steps: S1. Ultrasonic dispersion of nano zinc oxide in anhydrous ethanol, after uniform dispersion, adding γ-methacryloxypropyltrimethoxysilane, mixing evenly, adding hydrochloric acid to adjust the pH to 5, reacting, after the reaction is completed, filtering, washing with anhydrous ethanol, and vacuum drying at 60° C. for 12 h to obtain modified zinc oxide; S2, uniformly mixing modified zinc oxide, EPDM rubber, maleic anhydride and initiator, adding the mixture into a twin-screw extruder to react, and after the reaction is completed, discharging the mixture to obtain modified EPDM rubber; S3, adding nylon 6, modified EPDM rubber and antioxidant 168 into a twin-screw extruder for melt blending, and after the blending is completed, discharging the material to obtain EPDM rubber modified nylon 6; S4. Evenly mix nylon 6, EPDM rubber modified nylon 6, epoxy modified polytetrafluoroethylene, antioxidant, lubricant and dispersant in a high-speed mixer, transfer to a torque rheometer for melt blending, discharge, dry in a vacuum drying oven at 90°C for 12 hours, inject into an injection molding machine for sample preparation, cool, and obtain a urea tube.
[0007] As a further embodiment of the present invention, the antioxidant is a composite antioxidant, which is composed of antioxidant 1098 and antioxidant 1076 in a mass ratio of 3:1.
[0008] As a further embodiment of the present invention, the lubricant is zinc stearate.
[0009] As a further embodiment of the present invention, the dispersant is ethylene bisstearamide.
[0010] As a further embodiment of the present invention, the mass ratio of nano zinc oxide, anhydrous ethanol and γ-methacryloxypropyltrimethoxysilane in S1 is 100:(2400-3000):(48-75).
[0011] As a further embodiment of the present invention, the reaction temperature in S1 is 70-80° C., and the reaction time is 12-18 h.
[0012] As a further embodiment of the present invention, the hydrochloric acid in S1 is a 10 wt % hydrochloric acid solution.
[0013] As a further embodiment of the present invention, the mass ratio of modified zinc oxide, EPDM rubber, maleic anhydride and initiator in S2 is (12-15):100:(18-25):(1-1.5).
[0014] As a further embodiment of the present invention, the initiator in S2 is dicumyl peroxide.
[0015] As a further solution of the present invention, in the twin-screw extruder in S2, the temperature of the die head is 180°C, the reaction temperature is 195-210°C, the screw speed is 150-350r / min, and the reaction time is 8-10min.
[0016] As a further embodiment of the present invention, the mass ratio of nylon 6, modified EPDM rubber and antioxidant 168 in S3 is 100:(10-25):(1-3).
[0017] As a further solution of the present invention, the temperature of the die in S3 is 190-210° C., the temperature of melt blending is 220-245° C., the time of melt blending is 5-8 min, and the screw speed is 300-450 r / min.
[0018] As a further scheme of the present invention, the preparation method of the epoxy-modified polytetrafluoroethylene is as follows: tert-butyl lithium, ethylenediamine and polytetrafluoroethylene resin in a mass ratio of 640:600:100 are uniformly mixed, activated for 0.5h at 0°C in a nitrogen atmosphere, filtered, washed with tetrahydrofuran, and dried to obtain an activated polytetrafluoroethylene resin, the activated polytetrafluoroethylene resin is added to anhydrous ethanol, and then glycidyl methacrylate is added, wherein the mass ratio of the activated polytetrafluoroethylene resin, anhydrous ethanol and glycidyl methacrylate is 100:4200:900, stirred and mixed, reacted at 80°C for 9h, after the reaction is completed, filtered, washed with anhydrous ethanol, and vacuum dried at 60°C for 12h to obtain epoxidized polytetrafluoroethylene.
[0019] As a further solution of the present invention, the temperature of melt blending in S4 is 320-340°C, the speed of the rotor is 90-120r / min, and the time of melt blending is 5-8min.
[0020] As a further solution of the present invention, in S4, the injection pressure is 80-90 MPa, the injection temperature is 330-350° C., the injection time is 10-15 s, the mold temperature is 35° C., and the cooling time is 45 s.
[0021] 3. Beneficial technical effects In the present invention, γ-methacryloxypropyltrimethoxysilane is used to modify nano zinc oxide, alkenyl groups are introduced on the surface of nano zinc oxide to obtain modified zinc oxide, and the modified zinc oxide, EPDM rubber and maleic anhydride are polymerized under the action of an initiator to obtain modified EPDM rubber. The anhydride groups on the modified EPDM rubber and the amino groups on nylon 6 undergo an amidation reaction to obtain EPDM rubber-modified nylon 6, and nylon 6, EPDM rubber-modified nylon 6, epoxy-modified polytetrafluoroethylene, an antioxidant, a lubricant and a dispersant are melt-blended to prepare a sample to obtain a urea tube.
[0022] Compared with the prior art, the present invention has the following beneficial effects: (1) In the present invention, nylon 6 is used as the matrix of the urea tube, which has high mechanical strength, corrosion resistance, rigidity and wear resistance, and is easy to process and shape. The prepared urea tube can withstand certain pressure and wear during use. Nano zinc oxide, as an additive, has excellent mechanical properties and can significantly improve the tensile strength and elastic modulus of the matrix material. At the same time, nano zinc oxide has excellent antibacterial properties, anti-aging properties and heat resistance, which can extend the service life of the urea tube. Nano zinc oxide is grafted onto EPDM rubber to avoid the agglomeration of nano zinc oxide in the matrix, has good dispersibility, and improves the overall performance of the composite material. The obtained material has excellent mechanical properties, antibacterial properties and anti-aging properties.
[0023] (2) The EPDM rubber in the present invention has excellent aging resistance, can resist the damage of environmental factors such as ozone and ultraviolet rays to the material, and has good stability to urea solution, and can maintain physical and chemical stability for a long time. At the same time, the EPDM rubber has good elasticity, can absorb the vibration and impact generated by the pipeline during use, and has excellent corrosion resistance, heat resistance, good elasticity and sealing performance, ensuring the sealing of the urea pipe at the connection. The obtained urea pipe has excellent folding resistance and effectively prevents leakage. Nylon 6 and modified EPDM rubber undergo amidation reaction to form a cross-linked network structure, which can absorb and disperse stress, further improve mechanical strength and toughness, introduce a large number of active groups, and further improve dispersibility. At the same time, after the EPDM rubber is modified, the processing performance is improved, the heat deformation temperature of the material is significantly increased, and stable performance can be maintained at higher temperatures, and the comprehensive performance of the urea pipe is improved.
[0024] (3) The polytetrafluoroethylene in the present invention has excellent corrosion resistance. When added to the matrix, it can withstand high-concentration urea solutions and prevent urea from corroding the pipe wall. It also has good high and low temperature resistance, ensuring the stability and safety of the urea pipe under extreme temperature conditions. The low friction coefficient of polytetrafluoroethylene helps to reduce the flow resistance of urea in the pipeline and improve the transportation efficiency. Its extremely low surface energy is not easy to adhere, and it can effectively prevent urea from depositing on the inner wall of the pipeline, thereby keeping the pipeline clean and unobstructed. The polytetrafluoroethylene is epoxidized to further enhance its surface activity. The introduced epoxy groups can react with nylon 6 and EPDM-modified nylon 6, enhancing the adhesion and compatibility between the materials. The urea pipe prepared after mixing has good processability and formability, and also has excellent corrosion resistance, heat resistance and mechanical properties. DETAILED DESCRIPTION
[0025] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0026] Embodiment 1: A method for preparing a urea tube comprises the following steps: S1. Ultrasonic dispersion of nano zinc oxide in anhydrous ethanol, after uniform dispersion, adding γ-methacryloxypropyltrimethoxysilane, wherein the mass ratio of nano zinc oxide, anhydrous ethanol and γ-methacryloxypropyltrimethoxysilane is 100:2400:48, mixing evenly, adding hydrochloric acid to adjust the pH to 5, reacting at 70°C for 18 hours, after the reaction is completed, filtering, washing with anhydrous ethanol, and vacuum drying at 60°C for 12 hours to obtain modified zinc oxide; S2, the mass ratio of 12:100:18:1 of modified zinc oxide, EPDM rubber, maleic anhydride and initiator dicumyl peroxide was mixed uniformly, added to a twin-screw extruder, reacted, during the reaction, the temperature of the die was 180 ° C, the reaction temperature was 195 ° C, the screw speed was 150r / min, the reaction time was 10min, after the reaction was completed, the material was discharged to obtain modified EPDM rubber; S3, adding nylon 6, modified EPDM rubber and antioxidant 168 in a mass ratio of 100:10:1 into a twin-screw extruder for melt blending, wherein the temperature of the die head is 190° C., the temperature of the melt blending is 220° C., the melt blending time is 8 min, the screw speed is 300 r / min, and after the blending is completed, the material is discharged to obtain EPDM rubber modified nylon 6; S4. Nylon 6, EPDM rubber modified nylon 6, epoxy modified polytetrafluoroethylene, antioxidant, lubricant zinc stearate, and dispersant ethylene bisstearamide in a mass ratio of 100:25:7:0.2:0.5:0.1 are mixed evenly in a high-speed mixer, wherein the antioxidant consists of antioxidant 1098 and antioxidant 1076 in a mass ratio of 3:1. The mixture is transferred to a torque rheometer for melt blending. The melt blending temperature is 320°C, the rotor speed is 90r / min, and the melt blending time is 8min. The material is discharged, dried in a vacuum drying oven at 90°C for 12h, and injected into an injection molding machine for sample preparation. The injection pressure is 80MPa, the injection temperature is 330°C, the injection time is 15s, the mold temperature is 35°C, and the cooling time is 45s to obtain a urea tube.
[0027] Embodiment 2: A method for preparing a urea tube comprises the following steps: S1. Ultrasonic dispersion of nano zinc oxide in anhydrous ethanol, after uniform dispersion, adding γ-methacryloxypropyltrimethoxysilane, wherein the mass ratio of nano zinc oxide, anhydrous ethanol and γ-methacryloxypropyltrimethoxysilane is 100:2800:65, mixing evenly, adding hydrochloric acid to adjust the pH to 5, reacting at 75°C for 14 hours, after the reaction is completed, filtering, washing with anhydrous ethanol, and vacuum drying at 60°C for 12 hours to obtain modified zinc oxide; S2, the mass ratio of 13:100:21:1.2 of modified zinc oxide, EPDM rubber, maleic anhydride and initiator dicumyl peroxide was mixed uniformly, added to a twin-screw extruder, reacted, during the reaction, the temperature of the die head was 180 ° C, the reaction temperature was 205 ° C, the screw speed was 300r / min, the reaction time was 9min, after the reaction was completed, the material was discharged to obtain modified EPDM rubber; S3, adding nylon 6, modified EPDM rubber and antioxidant 168 in a mass ratio of 100:15:1.8 into a twin-screw extruder for melt blending, wherein the temperature of the die head is 200° C., the temperature of the melt blending is 235° C., the melt blending time is 7 min, the screw speed is 350 r / min, and after the blending is completed, the material is discharged to obtain EPDM rubber modified nylon 6; S4. Nylon 6, EPDM rubber modified nylon 6, epoxy modified polytetrafluoroethylene, antioxidant, lubricant zinc stearate, and dispersant ethylene bisstearamide in a mass ratio of 100:32:9:0.4:0.8:0.3 are mixed evenly in a high-speed mixer, wherein the antioxidant consists of antioxidant 1098 and antioxidant 1076 in a mass ratio of 3:1. The mixture is transferred to a torque rheometer for melt blending. The melt blending temperature is 335°C, the rotor speed is 105r / min, and the melt blending time is 7min. The material is discharged, dried in a vacuum drying oven at 90°C for 12h, and injected into an injection molding machine for sample preparation. The injection pressure is 85MPa, the injection temperature is 345°C, the injection time is 12s, the mold temperature is 35°C, and the cooling time is 45s to obtain a urea tube.
[0028] Embodiment 3: A method for preparing a urea tube, comprising the following steps: S1, adding nylon 6, modified EPDM rubber and antioxidant 168 in a mass ratio of 100:21:1.8 into a twin-screw extruder for melt blending, wherein the temperature of the die head is 200° C., the temperature of the melt blending is 235° C., the melt blending time is 7 min, the screw speed is 350 r / min, and after the blending is completed, the material is discharged to obtain EPDM rubber modified nylon 6; S2. Nylon 6, EPDM rubber modified nylon 6, epoxy modified polytetrafluoroethylene, antioxidant, lubricant zinc stearate, and dispersant ethylene bisstearamide in a mass ratio of 100:32:9:0.4:0.8:0.3 are mixed uniformly in a high-speed mixer, wherein the antioxidant consists of antioxidant 1098 and antioxidant 1076 in a mass ratio of 3:1, and transferred to a torque rheometer for melt blending. The melt blending temperature is 335°C, the rotor speed is 105r / min, and the melt blending time is 7min. The material is discharged, dried in a vacuum drying oven at 90°C for 12h, and injected into an injection molding machine for sample preparation. The injection pressure is 85MPa, the injection temperature is 345°C, the injection time is 12s, the mold temperature is 35°C, and the cooling time is 45s to obtain a urea tube.
[0029] The preparation method of the modified EPDM rubber is the same as the preparation method of the modified EPDM rubber in Example 2.
[0030] Embodiment 4: A method for preparing a urea tube comprises the following steps:
[0031] S1. Nylon 6, EPDM rubber modified nylon 6, epoxy modified polytetrafluoroethylene, antioxidant, lubricant zinc stearate, and dispersant ethylene bisstearamide in a mass ratio of 100:40:10:0.4:0.8:0.3 are mixed uniformly in a high-speed mixer, wherein the antioxidant consists of antioxidant 1098 and antioxidant 1076 in a mass ratio of 3:1. The mixture is transferred to a torque rheometer for melt blending. The melt blending temperature is 335°C, the rotor speed is 105r / min, and the melt blending time is 7min. The material is discharged, dried in a vacuum drying oven at 90°C for 12h, and injected into an injection molding machine for sample preparation. The injection pressure is 85MPa, the injection temperature is 345°C, the injection time is 12s, the mold temperature is 35°C, and the cooling time is 45s to obtain a urea tube.
[0032] The preparation method of EPDM rubber modified nylon 6 is the same as the preparation method of EPDM rubber modified nylon 6 in Example 3.
[0033] Embodiment 5 A method for preparing a urea tube comprises the following steps: S1. Ultrasonic dispersion of nano zinc oxide in anhydrous ethanol, after uniform dispersion, adding γ-methacryloxypropyltrimethoxysilane, wherein the mass ratio of nano zinc oxide, anhydrous ethanol and γ-methacryloxypropyltrimethoxysilane is 100:3000:75, mixing evenly, adding hydrochloric acid to adjust the pH to 5, reacting at 80° C. for 12 h, after the reaction is completed, filtering, washing with anhydrous ethanol, and vacuum drying at 60° C. for 12 h to obtain modified zinc oxide; S2, the mass ratio of 15:100:25:1.5 of modified zinc oxide, EPDM rubber, maleic anhydride and initiator dicumyl peroxide was mixed uniformly, added to a twin-screw extruder, reacted, during the reaction, the temperature of the die head was 180 ° C, the reaction temperature was 210 ° C, the screw speed was 350r / min, the reaction time was 8min, after the reaction was completed, the material was discharged to obtain modified EPDM rubber; S3, adding nylon 6, modified EPDM rubber and antioxidant 168 in a mass ratio of 100:25:3 into a twin-screw extruder for melt blending, wherein the temperature of the die head is 210° C., the temperature of the melt blending is 245° C., the melt blending time is 5 min, the screw speed is 450 r / min, and after the blending is completed, the material is discharged to obtain EPDM rubber modified nylon 6; S4. Nylon 6, EPDM rubber modified nylon 6, epoxy modified polytetrafluoroethylene, antioxidant, lubricant zinc stearate, and dispersant ethylene bisstearamide in a mass ratio of 100:42:12:0.5:1:0.5 are mixed evenly in a high-speed mixer, wherein the antioxidant consists of antioxidant 1098 and antioxidant 1076 in a mass ratio of 3:1, and transferred to a torque rheometer for melt blending. The melt blending temperature is 340°C, the rotor speed is 120r / min, and the melt blending time is 5min. The material is discharged, dried in a vacuum drying oven at 90°C for 12h, and injected into an injection molding machine for sample preparation. The injection pressure is 90MPa, the injection temperature is 350°C, the injection time is 10s, the mold temperature is 35°C, and the cooling time is 45s to obtain a urea tube.
[0034] Comparative Example 1 A method for preparing a urea tube comprises the following steps: S1. Ultrasonic dispersion of nano zinc oxide in anhydrous ethanol, after uniform dispersion, adding γ-methacryloxypropyltrimethoxysilane, wherein the mass ratio of nano zinc oxide, anhydrous ethanol and γ-methacryloxypropyltrimethoxysilane is 100:2800:65, mixing evenly, adding hydrochloric acid to adjust the pH to 5, reacting at 75°C for 14 hours, after the reaction is completed, filtering, washing with anhydrous ethanol, and vacuum drying at 60°C for 12 hours to obtain modified zinc oxide; S2, the mass ratio of 13:100:21:1.2 of modified zinc oxide, ethylene propylene diene monomer rubber, glycidyl methacrylate and initiator dicumyl peroxide was mixed uniformly, added to a twin-screw extruder, reacted, during the reaction, the temperature of the die head was 180 ° C, the reaction temperature was 205 ° C, the screw speed was 300r / min, the reaction time was 9min, after the reaction was completed, the material was discharged to obtain epoxy modified ethylene propylene diene monomer rubber; S3. Nylon 6, epoxy-modified EPDM rubber, epoxy-modified polytetrafluoroethylene, antioxidant, lubricant zinc stearate, and dispersant ethylene bisstearamide in a mass ratio of 131.5:8.5:10:0.4:0.8:0.3 are mixed evenly in a high-speed mixer, wherein the antioxidant consists of antioxidant 1098 and antioxidant 1076 in a mass ratio of 3:1, and transferred to a torque rheometer for melt blending. The melt blending temperature is 335°C, the rotor speed is 105r / min, and the melt blending time is 7min. The material is discharged, dried in a vacuum drying oven at 90°C for 12h, and injected into an injection molding machine for sample preparation. The injection pressure is 85MPa, the injection temperature is 345°C, the injection time is 12s, the mold temperature is 35°C, and the cooling time is 45s to obtain a urea tube.
[0035] Comparative Example 2 A method for preparing a urea tube comprises the following steps: S1. Evenly mix EPDM rubber, maleic anhydride and initiator dicumyl peroxide in a mass ratio of 100:21:1.2, add the mixture into a twin-screw extruder, and react. During the reaction, the temperature of the die head is 180°C, the reaction temperature is 205°C, the screw speed is 300r / min, and the reaction time is 9min. After the reaction is completed, discharge the mixture to obtain maleic anhydride-modified EPDM rubber. S2, adding nylon 6, maleic anhydride modified EPDM rubber and antioxidant 168 in a mass ratio of 100:21:1.8 into a twin-screw extruder for melt blending, wherein the temperature of the die head is 200°C, the temperature of the melt blending is 235°C, the melt blending time is 7min, the screw speed is 350r / min, and after the blending is completed, the material is discharged to obtain EPDM modified nylon 6; S3. Nylon 6, EPDM rubber modified nylon 6, nano zinc oxide, epoxy modified polytetrafluoroethylene, antioxidant, lubricant zinc stearate, and dispersant ethylene bisstearamide in a mass ratio of 100:39:1:10:0.4:0.8:0.3 are mixed uniformly in a high-speed mixer, wherein the antioxidant consists of antioxidant 1098 and antioxidant 1076 in a mass ratio of 3:1. The mixture is transferred to a torque rheometer for melt blending. The melt blending temperature is 335°C, the rotor speed is 105r / min, and the melt blending time is 7min. The material is discharged, dried in a vacuum drying oven at 90°C for 12h, and injected into an injection molding machine for sample preparation. The injection pressure is 85MPa, the injection temperature is 345°C, the injection time is 12s, the mold temperature is 35°C, and the cooling time is 45s to obtain a urea tube.
[0036] Comparative Example 3 A method for preparing a urea tube comprises the following steps: S1. Nylon 6, EPDM rubber modified nylon 6, antioxidant, lubricant zinc stearate, and dispersant ethylene bisstearamide in a mass ratio of 110:40:0.4:0.8:0.3 are mixed uniformly in a high-speed mixer, wherein the antioxidant consists of antioxidant 1098 and antioxidant 1076 in a mass ratio of 3:1. The mixture is transferred to a torque rheometer for melt blending. The melt blending temperature is 335°C, the rotor speed is 105r / min, and the melt blending time is 7min. The material is discharged, dried in a vacuum drying oven at 90°C for 12h, and injected into an injection molding machine for sample preparation. The injection pressure is 85MPa, the injection temperature is 345°C, the injection time is 12s, the mold temperature is 35°C, and the cooling time is 45s to obtain a urea tube.
[0037] The preparation method of EPDM rubber modified nylon 6 is the same as the preparation method of EPDM rubber modified nylon 6 in Example 3.
[0038] The preparation method of epoxy-modified polytetrafluoroethylene in the embodiments and comparative examples of the present invention is as follows: tert-butyl lithium, ethylenediamine and polytetrafluoroethylene resin in a mass ratio of 640:600:100 are uniformly mixed, activated for 0.5h at 0°C in a nitrogen atmosphere, filtered, washed with tetrahydrofuran, and dried to obtain an activated polytetrafluoroethylene resin, the activated polytetrafluoroethylene resin is added to anhydrous ethanol, and then glycidyl methacrylate is added, wherein the mass ratio of the activated polytetrafluoroethylene resin, anhydrous ethanol and glycidyl methacrylate is 100:4200:900, stirred and mixed, reacted at 80°C for 9h, after the reaction is completed, filtered, washed with anhydrous ethanol, and vacuum dried at 60°C for 12h to obtain epoxidized polytetrafluoroethylene.
[0039] The nano zinc oxide in the present invention was purchased from Nanjing Baoket New Materials Co., Ltd., model PZT-30, and the average particle size was 30nm; EPDM rubber was purchased from Yisu Technology Co., Ltd., the brand is Sinopec Mitsui, model 3092; antioxidant 168, antioxidant 1098 and antioxidant 1076 were all purchased from BASF (China) Co., Ltd.; nylon 6 was purchased from Suzhou Aoxuan Engineering Plastics Co., Ltd., item number YH3400; polytetrafluoroethylene resin was purchased from Daikin Industries, Ltd., model M-18; zinc stearate was purchased from Jiangxi Hongyuan Chemical Co., Ltd.; ethylene bisstearamide was purchased from South Korea Shinwon Chemical Co., Ltd.; other unspecified raw materials and reagents are commercially available.
[0040] The urea tubes prepared in Examples 1-5 and Comparative Examples 1-3 were tested accordingly, and the test methods and test results are as follows: (1) Urea resistance test: Check whether the appearance of the sample is good. Cut the urea tube sample into a specimen with a length of 150 mm, measure the initial length L0 and weight m0, immerse the sample in a sufficient amount of urea solution with a concentration of 32.5%, and then put it in an oven at 85°C for 500 hours. After the test, clean the sample. After the sample is dried, check whether the appearance of the sample is good. Measure the length L1 and weight m1, and calculate the change rate of size and weight. The calculation method is as follows: size change rate = (L1-L0) / L0×100%; weight change rate = (m1-m0) / m0×100%; (2) Tensile test: The urea tube samples prepared in each embodiment and comparative example before and after the urea resistance test were cut into 6.5 mm specimens, both ends of the specimens were fixed on a tensile testing machine, and an extensometer was fixed on the specimens, and then a tensile test was performed at a speed of 50 mm / min; (3) Bending performance test: After the urea resistance test, refer to the industry standard of urea pipes. The test standard is ≤30mm and can move freely, which is qualified; The above test results are shown in Table 1: Table 1 Test items Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Comparative Example 2 Comparative Example 3 Dimensional change rate (%) 0.85 0.51 0.38 0.15 0.49 1.43 1.75 3.72 Quality change rate (%) 1.97 1.10 1.03 0.92 1.18 2.06 2.93 4.50 Appearance good good good good good good Cracking Cracking Tensile strength (MPa) 30.1 35.6 36.2 36.9 35.8 34.5 28.6 35.9 Elongation at break (%) 315 354 368 381 375 368 307 341 Tensile strength after treatment (MPa) 26.0 32.8 33.5 34.2 32.4 30.2 23.1 30.7 Elongation at break after treatment (%) 289 330 348 363 344 331 265 302 Bending test qualified qualified qualified qualified qualified qualified Failure qualified According to the test results of Table 1, it can be seen that the urea tubes corresponding to Examples 1-5 have excellent corrosion resistance, mechanical properties, heat resistance and folding resistance. After the urea resistance test, the size change rate and weight change rate of the samples corresponding to Examples 1-5 are small, and the appearance is still good, indicating that the corrosion resistance is good. Before and after the urea resistance test, the samples are respectively tested for tensile properties and bending properties, wherein the bending properties tests of the samples corresponding to Examples 1-5 are all qualified, and the folding resistance is good. Before urea treatment, the tensile strength of the sample corresponding to Example 4 can still reach 36.9MPa, and the elongation at break is 381%. After urea treatment, the tensile strength can still reach 34.2MPa, and the elongation at break is 363%, indicating that the heat resistance is good, and after urea and high temperature treatment, the tensile strength and elongation at break change less. In Comparative Example 2, nano zinc oxide is not processed, and the dispersibility and compatibility are greatly reduced, and the comprehensive performance is greatly reduced. In Comparative Example 3, polytetrafluoroethylene was not added, the hydrophobicity was greatly reduced, the dimensional change rate and weight change rate were large, and before being treated with urea and high temperature, the effect on the mechanical properties was small. After the treatment, the mechanical properties were greatly reduced.
[0041] In addition, the urea pipe can be used in conjunction with an external heating component to heat both urea and diesel, and is suitable for use in relatively cold regions.
[0042] Although the embodiments of the present invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that all equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the present invention.
Claims
1. A urea tube, characterized in that: The raw materials include the following parts by weight: 100 parts of nylon 6, 25-42 parts of EPDM rubber modified nylon 6, 7-12 parts of epoxy modified polytetrafluoroethylene, 0.2-0.5 parts of antioxidant, 0.5-1 parts of lubricant, and 0.1-0.5 parts of dispersant; The urea tube is prepared by the following steps: S1. Ultrasonic dispersion of nano zinc oxide in anhydrous ethanol, after uniform dispersion, adding γ-methacryloxypropyltrimethoxysilane, mixing evenly, adding hydrochloric acid to adjust the pH to 5, reacting, after the reaction is completed, filtering, washing, and vacuum drying at 60° C. for 12 h to obtain modified zinc oxide; S2, uniformly mixing modified zinc oxide, EPDM rubber, maleic anhydride and initiator, adding the mixture into a twin-screw extruder to react, and after the reaction is completed, discharging the mixture to obtain modified EPDM rubber; S3, adding nylon 6, modified EPDM rubber and antioxidant 168 into a twin-screw extruder for melt blending, and after the blending is completed, discharging the material to obtain EPDM rubber modified nylon 6; S4. Evenly mix nylon 6, EPDM rubber modified nylon 6, epoxy modified polytetrafluoroethylene, antioxidant, lubricant and dispersant in a high-speed mixer, transfer to a torque rheometer for melt blending, discharge, vacuum dry at 90°C for 12h, inject into an injection molding machine for sample preparation, cool, and obtain a urea tube.
2. A urea pipe according to claim 1, characterized in that: The antioxidant is a composite antioxidant, which is composed of antioxidant 1098 and antioxidant 1076 in a mass ratio of 3:
1.
3. A urea tube according to claim 1, characterized in that: The lubricant is zinc stearate.
4. A urea tube according to claim 1, characterized in that: The dispersant is ethylene bisstearamide.
5. A urea pipe according to claim 1, characterized in that: The mass ratio of modified zinc oxide, EPDM rubber, maleic anhydride and initiator in S2 is (12-15):100:(18-25):(1-1.5).
6. A urea tube according to claim 1, characterized in that: In the twin-screw extruder in S2, the temperature of the die head is 180°C, the reaction temperature is 195-210°C, the screw speed is 150-350r / min, and the reaction time is 8-10min.
7. A urea tube according to claim 1, characterized in that: The mass ratio of nylon 6, modified EPDM rubber and antioxidant 168 in S3 is 100:(10-25):(1-3).
8. A urea tube according to claim 1, characterized in that: The temperature of the die in S3 is 190-210° C., the temperature of melt blending is 220-245° C., the time of melt blending is 5-8 min, and the screw speed is 300-450 r / min.
9. A urea tube according to claim 1, characterized in that: The temperature of melt blending in S4 is 320-340° C., the speed of the rotor is 90-120 r / min, and the time of melt blending is 5-8 min.
10. A urea pipe according to claim 1, characterized in that: In the S4, the injection pressure is 80-90 MPa, the injection temperature is 330-350° C., the injection time is 10-15 s, the mold temperature is 35° C., and the cooling time is 45 s.
Citation Information
Patent Citations
Ultraviolet light crosslinked EPT rubber cable insulation material and preparation thereof
CN101434728A
Urea tube and production process thereof
CN102585380A
Urea pipe
CN107725917A
Preparation method of lubricating resin composition
CN116082837A
Halogen-free flame-retardant PPO composite material and preparation method thereof
CN117362979A